The therapeutic effect of nano-zinc on the optic nerve of offspring rats and their mothers treated with lipopolysaccharides. Issue 1 (31st December 2023) - Emara, Eman Mohammed; El-Sayyad, Hassan Ih; Mowafy, Amr M; El-Ghaweet, Heba a
ABSTRACT: This study investigated the toxicity of lipopolysaccharides (LPS) and the therapeutic role of zinc oxide nanoparticles (ZnO NPs) on the optic nerve of mother rats and their offspring treated with LPS. This study used eight male and forty female rats ( Rattus norvegicus ). Following mating, pregnant rats were separated into four groups: controls, LPS, ZnO NPs and LPS and ZnO NP-treated groups. LPS was injected twice during pregnancy. ZnO NPs were injected three times duringpregnancy, and a dose after birth. Mother rats and their offspring at 21daysold were sacrificed and separated from their optic nerve for histological and immunohistochemical examinations. Collected blood was collected from the mother rat for biochemical examination to evaluate superoxide dismutase-1 (SOD-1), catalase and malondialdehyde (MDA). This study discovered that ZnO NPs improved the histology of the optic nerve, decreased Cyclooxygenase-2 (COX-2) immunostaining, which overexpressed in the optic nerve of rats receiving LPS treatment and increased MDA. ZnO NPs also decreased the levels of the antioxidant enzymes such as SOD-1 and catalase, which had increased in the LPS-treated group. In conclusion, ZnO NPs injection into mother rats treated with LPS alleviated the markers of optic nerve injury in its offspring due to their antioxidant and neuroprotective effect.